Management accounting practices, governing boards and competitive advantage of Ugandan secondary schools - Korutaro Nkundabanyanga, Stephen; Muhwezi, Moses; Tauringana, Venancio (International Journal of Educational Management, 2018)
This paper reports on the results of a study carried out to determine the use of Management Accounting Practices (MAPR) in Ugandan secondary schools. The study also sought to determine whether MAPR and governing boards (board size, gender diversity and frequency of board meetings) influence the perceived competitive advantage. Design/methodology/approach - This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 200 secondary schools. The data was analysed through ordinary least squares regression using Statistical Package for Social Scientists. Findings - There are wide variations in MAP in terms of the extent to which the schools employ management accounting techniques. Also, MAP and governing boards have a predictive force on the schools’ competitive advantage. However, governing board’s size has no effect on competitive advantage. In terms of the control variables, the results suggest that while government school ownership has a positive effect on competitive advantage, the school’s size has no effect. There are intertwining relationships of frequency of board meetings, board size and school size. Result limitations/Implications- The present study was limited to the secondary schools in Uganda which limits generalizability. Still, the results offer important implications for secondary schools’ governing boards, owners and for similar African governments who are a major stakeholder in the secondary school education system. The exact mechanism by which intertwining relationships of frequency of board meetings, board size and school size impact competitive advantage is not been explored in this paper. Future researchers may direct research effort in this endeavour.
Keywords: Management accounting practices; Governing boards; Competitive advantage